Lived experiences of the elderly under institutional care: a case of Batanai Old Age Home, Gweru, Zimbabwe - Tarugarira, Precious V. (Midlands State University, 2016)
The purpose of the study was to explore the lived experiences of the elderly under institutional care at Batanai Old Age Home in Gweru, Zimbabwe. The research explored the lives of the residents taking note of the reasons behind their admission into the institution, the positive and negative aspects of staying in an institution. The study also looked at the coping strategies that they adopted and the support systems required in nursing homes to ensure the wellbeing of the residents.The target population consisted of 10 residents at Batanai Old Age Home. Purposive sampling procedure was used and thus, 7 residents were found to be eligible for the interviews. The sample consisted of both males and females. Data was collected through the use of in-depth semi-structured interviews with 7 participants. The researcher used Thematic Analysis to analyze the data.